Answer:
[tex]\large\boxed{y=\dfrac{1}{2}x+1}[/tex]
Step-by-step explanation:
[tex]\text{The slope-intercept form of an equation of a line:}\\\\y=mx+b\\\\m-slope\\b-y-intercept\\\\\text{We have:}\ m=\dfrac{1}{2}\ \text{and the point}\ (6,\ 4).\\\\\text{The equation:}\ y=\dfrac{1}{2}x+b.\\\\\text{Put the coordinates of the point to the equation:}\\\\4=\dfrac{1}{2}(6)+b\\\\4=3+b\qquad\text{subtract 3 from both sides}\\\\1=b\to b=1\\\\\text{Finally:}\\\\y=\dfrac{1}{2}x+1[/tex]
Imagine each letter of the word “Mathematical” is written on individual pieces of paper and placed in a bag. Should you pick a random letter from that bag, what is the probability that you pick a vowel?
In the word "Mathematical"
Vowels are "a", "e", "a", "i", "a" from left to right
Consonants are "m", "t", "h", "m", "t", "c", "l"
5 vowels and 7 consonants of total 12 letters
So the probability of picking a vowel is
[tex] \frac{5}{12} [/tex]
Answer:
The probability to pick a vowel is [tex]\frac{5}{12} }[/tex]
Step-by-step explanation:
Probability = Required outcome / All possible outcome
From the question;
the word “Mathematical” is written on individual pieces of paper
We have to count the total numbers of letter present in the word
When we count properly, we have 12 total numbers of letters
The we proceed to count the numbers of vowel
Here are the vowel in the word “Mathematical” :
a, e, a, i, a
The vowels are 5 letters
Probability = Required outcome / All possible outcome
Required outcome = 5
All possible outcome = 12
Probability = [tex]\frac{5}{12} }[/tex]
The probability that you pick a vowel is [tex]\frac{5}{12} }[/tex]
Which values of a and b make the following equation true? (5x7y2)(-4x4y5)=-20xayb
Answer:
The values of a and b are a = 11 , b = 7
Step-by-step explanation:
* Lets explain how to solve the problem
* In the exponential functions we have some rules
1- In multiplication if they have same base we add the power
# Ex: b^m × b^n = b^(m + n) ⇒ b is the base , m and n are the powers
2- In division if they have same base we subtract the power
# Ex: b^m ÷ b^n = b^(m – n) ⇒ b is the base , m and n are the powers
3- If we have power over power we multiply them
# Ex: (b^m)^n = b^(mn) ⇒ b is the base , m and n are the powers
* Lets solve the problem
∵ The equation is [tex](5x^{7}y^{2})(-4x^{4}y^{5})=-20x^{a}y^{2}[/tex] ⇒ (1)
- At first multiply the coefficients
∵ -4 × 5 = -20
- Multiply the base x
∵ [tex](x^{7})(x^{4})=x^{7+4}=x^{11}[/tex]
- Multiply the base y
∵ [tex](y^{2})(y^{5})=y^{2+5}=y^{7}[/tex]
∴ [tex](5x^{7}y^{2})(-4x^{4}y^{5})=-20x^{11}y^{7}[/tex] ⇒ (2)
- By comparing (1) and (2)
∴ a = 11 and b = 7
* The values of a and b are a = 11 , b = 7
What is the angle of elevation of the sun if a 45 foot tall flag pole casts a 22 foot long shadow?
Answer:
=63.9°
Step-by-step explanation:
To find the angle of elevation using the shadow of an object, we use the trigonometric ratio Tangent.
Tan∅=opposite/adjacent
Opposite is the height of pole while adjacent is the shadow of the pole.
The tan of the angle of elevation= height of the pole/length of shadow
Tan ∅=45/22
∅= Tan⁻¹(45/22)
=63.9°
Angle of elevation=63.9°
Plants are the major source of what biochemical needed in your diet? What specifically is this biochemical used for, and how is it broken down during digestion?
Carbohydrates. Carbohydrates are digested in the mouth, stomach and small intestine. Carbohydrase enzymes break down starch into sugars. The saliva in your mouth contains amylase, which is another starch digesting enzyme.
A 3-digit numeral is formed by selecting digits at random from 2,4,6,7 without repetition. Find the probability that the number formed contains only even digits. P(even digits)
Answer:
3/4.
Step-by-step explanation:
Total number of ways to pick 3 digits from the 4 given digits = 4P3
= 4!/ 1! = 24 ways.
The odd numbers are formed when 7 is the last digit of the 3 digits and this will be in 6 numbers 247, 267, 427, 467, 647 and 627 . So there will be 24 - 6 = 18 even numbers.
So the probability of only even digits = 18/24 = 3/4.
In your quilt shop,you make and sell quilts. You like to have a total of 26 yards of royal blue fabric in stock at the beginning of each month. Today your inventory includes 4 pieces of this fabric that are each 22 1/2 inches long and 3 pieces that are each 33 inches long. You must purchase this fabric in 3 yard long pieces. To replenish your stock,how many pieces do you need to buy?
Answer:
7 pieces
Step-by-step explanation:
Stock that must be available at the beginning of each month = 26 yards
Since,
1 yard = 36 inches
26 yards = 26 x 36 = 936 inches
This means 936 inches of fabric must be available at beginning of each month.
Current Inventory:
4 pieces that are each 22 1/2 (or 22.5) inches long. So total length of these fabrics = 4 x 22.5 = 90 inches
3 pieces that each 33 inches long. So total length of these fabrics = 3 x 33 = 99 inches
Therefore, the total length of current inventory = 90 + 99 = 189 inches.
Length of fabric needed more:
Length of fabric that must be bought more = 936 - 189 = 747 inches
It is given that the fabric must be bought in pieces are the 3 yards long. 3 yards is equal to 108 inches.
So, I have to buy pieces that are each 108 inches long and I need to complete 747 inches in total.
Therefore, the number of pieces that I need to buy = [tex]\frac{747}{108}=6.9[/tex]
Since, the pieces cannot be bought in fraction, I need to buy 7 complete pieces to replenish my stock.
You need to purchase 7 pieces of 3-yard fabric.
To determine how many pieces of fabric you need to buy, follow these steps:
Calculate your current inventory:4 pieces at [tex]22 \frac{1}{2}[/tex] inches each:Therefore, you need to purchase 7 pieces of fabric to replenish your stock.
How do I figure this one out whats the answer
Look at the picture
Given the functions f(x) = x^2 - 2x - 4 and g(x) = 2x - 4, at what values of x do f(x) and g(x) intersect?
Answer:
* The values of x are 0 and 4
Step-by-step explanation:
* Lets explain how to solve the problem
- f(x) = x² - 2x - 4 is a quadratic function
- g(x) = 2x - 4
∵ f(x) and g(x) are intersected
∴ They meet each other in a point
- To find this point equate the two functions
∵ f(x) = g(x)
∵ f(x) = x² - 2x - 4
∵ g(x) = 2x - 4
∴ x² - 2x - 4 = 2x - 4 ⇒ subtract 2x from both sides
∴ x² - 4x - 4 = -4
- Add 4 to both sides
∴ x² - 4x = 0
- Take x as a common factor
∴ x(x - 4) = 0
- Equate each factor by 0
∴ x = 0
- OR
∴ x - 4 = 0 ⇒ add 4 to both sides
∴ x = 4
∴ f(x) and g(x) intersected at x = 0 and x = 4
* The values of x are 0 and 4
PLZ HELP!!! WILL GIVE BRAINLIEST
Paul wants to visit his aunt who lives 300 miles away from his house. He drives his car at about 50 miles/hour. If x represents the time spent driving and y represents the distance from his aunt’s house, which scatter plot could represent this situation?
The solution is, It would take 6 hours, to visit his aunt who lives.
What is speed?
Speed is measured as distance moved over time. The formula for speed is speed = distance ÷ time. To work out what the units are for speed, you need to know the units for distance and time. In this example, distance is in metres (m) and time is in seconds (s), so the units will be in metres per second (m/s).
Speed = Distance/ Time.
here, we have,
given that,
Paul wants to visit his aunt who lives 300 miles away from his house. He drives his car at about 50 miles/hour.
If x represents the time spent driving.
then, we get,
An equation for that could be:
50x = 300 (X is how long it would take)
So, 50 mph• X (time spent) = 300 miles
now, we have,
50x = 300
or, x = 300/50
or, x = 6
Hence, The solution is, It would take 6 hours, to visit his aunt who lives.
To learn more on speed click:
brainly.com/question/28224010
#SPJ3
simplify the expression below
[tex]\sqrt{\dfrac{3}{15x}}=\sqrt{\dfrac{1}{5x}}=\dfrac{1}{\sqrt{5x}}=\dfrac{\sqrt{5x}}{5x}[/tex]
Which statements describe one of the transformations performed on f(x) = x^2
to create g(x) = 2x^2 +5?
Answer:
vertically stretched by a factor of 2 and moved up 5 units
Step-by-step explanation:
f(x)=x^2
f(x+5) means it moved left 5 units.
f(x-5) means it moved right 5 units.
f(x)+5 means it moved up 5 units.
f(x)-5 means it moved down 5 units.
One of the transformations we have is that it moved up 5 units.
m(x)=f(x)+5
m(x)=x^2+5
Now there is another transformation.
f(x)=x^2
a*f(x) means it is either being vertically stretched or compressed. a also tells if we have a reflection (if a is negative) or not (if a is positive).
n(x)=2x^2 means it has been vertically stretched by a factor of 2.
Let's put it altogether.
g(x)=2x^2+5
means the parent function has been vertically stretched by a factor of 2 and moved up 5 units
The transformations applied to f(x) to create g(x) involve a vertical stretching by a factor of 2 and a vertical shift upward by 5 units. These modifications result in a parabolic curve that is steeper and shifted upwards compared to the original f(x).
To transform the function [tex]f(x) = x^2[/tex] into [tex]g(x) = 2x^2 + 5,[/tex] several alterations are made.
First, the function is scaled vertically by a factor of 2.
This means that the output values of g(x) are twice as large as those of f(x) for any given input.
This vertical stretching increases the steepness of the parabolic curve.
Secondly, a constant term of 5 is added to g(x).
This shifts the entire graph of the function vertically upward by 5 units, creating an upward shift.
Consequently, g(x) is now centered 5 units above f(x).
For similar question on vertical stretching.
https://brainly.com/question/28321065
#SPJ3
I live - Villal
Use the distributive property to simplify this
expression:-2(3x+x-5)
1. Using order of operations, combine like terms
in the parentheses:
-2(4x + 5)
2. Distribute -2 to each term in the
parentheses:
What is the simplified algebraic expression?
O 4x-5
08x-5
O 8x + 10
O 8x - 10
-2(4x + 5)
Answer:
-8x+10
Step-by-step explanation:
The expression is: -2(3x+x-5)
Step 1: Using order of operations, combine like terms
-2(4x-5)
Step 2: Distribute -2 to each term in the parentheses:
-8x+10
Hence, the simplified expression is:
-8x+10
Answer:
-8x+10
Step-by-step explanation:
on edge
If y varies directly as x, and y = 2 when x = 8, then the constant of variation is :1/4 1/8 4 8
Answer:
1/4
Step-by-step explanation:
y varies directly as x means you should translate this as y=kx.
y varies indirectly as x means you should translate this as y=k/x.
Anyways we had directly, so the equation is of the form y=kx for any point (x,y) where k is the constant.
We are given y=kx and that this equation should satisfy (x,y)=(8,2).
So let's plug in 8 for x and 2 for y giving us
2=k*8
Divide both sides by 8:
2/8=k
Simplify:
1/4=k
So k is a constant, that constant, the never changing number, for the point (x,y) is 1/4.
That means the equation is y=1/4 *x. The 1/4 is the constant of variation, also called the constant of proportionality.
The constant of variation, in this case, is found to be 1/4 using the formula y = kx.
The constant of variation in this case is 1/4.
Given that y varies directly as x and y = 2 when x = 8, we can use the formula y = kx to find the constant of variation.
By substituting the values y = 2 and x = 8 into the formula, we get 2 = k * 8, which simplifies to k = 1/4.
What is the equation of the following line? Be sure to scroll down first to see
all answer options.
what are the real number solutions for x^2-3x+8=0
Answer:
There is no real solutions
Step-by-step explanation:
We have to count delta:
∆=(-3)²-4*8*1=-23.
Because ∆ is less than zero, your equation has only 2 imaginary solutions.
This equation hasn't got any real solutions (because √∆ isn't real)
Answer:
There are 0 real number solutions.
Step-by-step explanation:
You can use the discriminant to find the number of real number solutions.
The discriminant equation is:
[tex] {b}^{2} - 4ac[/tex].
a=1
b=-3
c=8
If the discriminant is positive, there are 2 real number solutions. If the discriminant is negative, there are 0 real number solutions. If the discriminant is 0, there is 1 real number solution.
[tex] {( - 3)}^{2} - 4(1)(8)[/tex]
= 9 - 32
= -23
The discriminant is negative.
0 real number solutions.
cos2a=2cos^2a-1 for all of a
true or false?
[tex]\bf ~\hspace{10em}\textit{Double Angle Identities}\\\\ sin(2\theta)=2sin(\theta)cos(\theta) ~\hfill cos(2\theta)= \begin{cases} cos^2(\theta)-sin^2(\theta)\\ 1-2sin^2(\theta)\\ \boxed{\bf 2cos^2(\theta)-1} \end{cases} \\\\\\ tan(2\theta)=\cfrac{2tan(\theta)}{1-tan^2(\theta)}[/tex]
well, take a peek at the cos(2θ) identities.
Add the equations.
2x-3y = -1
+ 3x + 3y= 26
Answer:
The answer in the procedure
Step-by-step explanation:
we have
2x-3y=-1 ----> equation A
3x+3y=26 --> equation B
Solve the system by elimination
Adds equation A and equation B
2x-3y=-1
3x+3y=26
----------------
2x+3x=-1+26
5x=25
x=25/5
x=5
Find the value of y
substitute the value of x in equation A or equation B and solve for y
2(5)-3y=-1
10-3y=-1
3y=10+1
y=11/3
Answer:
5x=25
Step-by-step explanation:
A p e x
What is solution to this inequality -13x>-39
Answer:
(-inf, 3)
Step-by-step explanation:
-13x > - 39
Multiply by -1/13, and flip the inequality.
x < 3
Answer:
[tex]\huge\boxed{x<3}[/tex]
Step-by-step explanation:
Multiply -1 both sides.
[tex]\displaystyle (-13x)(-1)<-39(-1)[/tex]
Solve.
[tex]\displaystyle 13x<39[/tex]
Divide by 13 both sides.
[tex]\displaystyle\frac{13x}{13}<\frac{39}{13}[/tex]
Simplify, to find the answer.
[tex]\displaystyle 39\div13=3[/tex]
[tex]\displaystyle x<3[/tex], which is our answer.
The owner of a chain of clothing stores is comparing the monthly profit earned in the past year from four different store locations. She calculated the mean and standard deviation of the monthly profit, in dollars, for each location, as shown in the table.
For which store location does 68% of the data lie between $19,371.18 and $22,295.48?
Answer:
Answer choice C, location C
Step-by-step explanation:
If you add or subtract the standard deviation to the monthly profit, then you get $19,371.18 and $22,295.48. This shows that the deviation withholds most of the data given
The store location for which [tex]68%[/tex]% of the data lies between $19,371.18 and $22.295.48 is location C
What is standard deviation?
Standard deviation explains the relation of data with mean.
How to find the location of the data?
For normal distributions, 68% of the data lies under one SD from the mean. Two standard deviations is within 95%, and three standard deviations would take up to 99%.
This implies that on taking (mean + SD) and (mean - SD), 68% of data would cover these two numbers.
Add and subtract SD from the mean to check which location will give $19,371.18 and $22.295.48.
For location A, we have
M-SD=23,124.70-1553.43=21,571.27
M SD = 23,124.70 + 1,553.43 = 24,678.4
For location B, we have
M - SD = 24,842.18 - 1,617.20 = 23,224.98
M + SD = 24, 842.18 + 1,617.20 = 26,459.38
For location C, we have
M - SD = 20,833.33 - 1,462.15 = 19,371.18
M + SD = 20,833.33 + 1,462.15 = 22,295.48
This implies the store location is C
Learn more about standard deviation here:
https://brainly.com/question/475676
#SPJ2
15
Ellen is currently twice as old as Maria, but in
6 years, Maria will be 2/3 as old as Ellen. How old is
Ellen now?
16
If 2x - 2y = 5 and x + y = 6, what is the value
How do I do this?
Answer:
15) Ellen is 12 years old.
16) Don't know what value you are looking for but x=(17/4) while y=(7/4) since the set of equations is 2x-2y=5 and x+y=6.
Step-by-step explanation:
15) Ellen (E) is currently twice as old as Maria (M).
Twice means to multiply by 2.
E=2M is therefore the equation for this part of the problem.
In 6 years, Maria (M) will be 2/3 as old as Ellen (E). Keep in my Maria as aged 6 years (M+6) and Ellen as aged 6 years (E+6):
M+6=(2/3)(E+6).
So we have this system to solve:
E=2M
M+6=(2/3)(E+6).
I'm going to replace the E in the second equation with 2M since the first equation says E=2M:
M+6=(2/3)(E+6) with E=2M:
M+6=(2/3)(2M+6)
Distribute:
M+6=(4/3)M+(12/3)
Reducing 12/3 to 4:
M+6=(4/3)M+4
Subtract 4 on both sides:
M+2=(4/3)M
Subtract M on both sides:
2=(4/3)M-M
Find a common denominator:
2=(4/3)M-(3/3)M
Combine like terms:
2=(1/3)M
Multiply both sides by the reciprocal of 1/3 which is 3:
3(2)=3(1/3)M
6=1M
6=M
M=6
Maria is six years old.
Recall E=2M.
So if M=6, then E=2(6)=12.
So currently E is twice as old as M since 6(2)=12.
In six years, M will be 12 which E will be 18.
M (12) is two-thirds as old as E (18) since 12=2/3(18)
16)
2x-2y=5
x + y=6
Your question doesn't state which value it is looking for.
Anyways I'm going to solve the system for the point (x,y) and then you can decide which part of this answer to use.
I'm going to solve this system by elimination. Each equation already has the same form: ax+by=c. I just need a column with the variables to be opposite or the same.
I'm going to multiply both sides of equation 2 by 2:
2x-2y=5
2x+2y=12
Now I have opposites in a column: -2y and 2y.
When you add opposites you get 0 so this is what you want to use elimination.
We are going to add the equations now:
2x-2y=5
2x+2y=12
------------------Adding!
4x+0y=17
4x =17
Divide both sides by 4:
x =17/4
Now if x=17/4 and x+y=6, then we have that (17/4)+y=6.
Subtracting 17/4 on both sides gives us y=6-(17/4).
Finding a common denominaotr gives us y=(24/4)-(17/4).
Simplifying this gives us y=(7/4).
The point of intersection (the solution) is (17/4 , 7/4)
The question is about solving two mathematical problems. The first problem is about ages, where Ellen is found to be 12 years old and Maria is six years old. The second problem is solving a linear equation system where the solution is x = 5 and y = 1.
Explanation:
Let's denote Maria's age as X and Ellen's age as Y. According to the problem, Ellen is twice as old as Maria, so that we can write Y = 2X. Maria will be 2/3 as old as Ellen in six years, so we can write another equation as X + 6 = 2/3 * (Y + 6). Now, we solve these equations. Substituting Y = 2X into the second equation, we get X + 6 = 2/3 * (2X + 6). Solving this, we find X = 6, so Maria is 6. Substituting X = 6 into Y = 2X, we find Y = 12, so Ellen is 12 years old.
For the second part of the problem, we solve the system of equations 2x - 2y = 5 and x + y = 6. One way is to take the second equation and solve for x: x = 6 - y. Substituting this into the first equation, we get 2*(6-y) - 2y = 5. Solving this simplifies to y = 1. Then, covering y = 1 into x + y = 6, we find x = 5.
Learn more about Solving Equations here:https://brainly.com/question/29050831
#SPJ3
need help here
who is right?
Step-by-step explanation:
Olivia is correct. Each O is opposite of the angle θ, and each A is adjacent.
Paula's first triangle was correct. But on the second triangle, she reversed the O and A.
Cathy's customer base is 2/3 residential and 1/3 business. If she has 350 residential customers, how many total customers does she have?
Answer:
Step-by-step explanation:
Why did I get different answers to find x?
The first one I used Soh Cah Toa and the second one I used laws of sines
[tex]\bf tan(39^o)=\cfrac{\stackrel{opposite}{x}}{\stackrel{adjacent}{8}}\implies 8\cdot tan(39^o)=x\implies 6.48\approx x \\\\[-0.35em] ~\dotfill\\\\ \cfrac{sin(39^o)}{x}=\cfrac{sin(51^o)}{8}\implies \cfrac{8\cdot sin(39^o)}{sin(51^o)}=x\implies 6.48\approx x[/tex]
one thing to bear in mind is that calculators have two modes, Degree mode and Radian mode, if your calculator is in Radian mode and you plug in tan(39), it thinks "tangent of 39 radians" and so it gives that, bearing in mind that 1 radian is about 57°.
So make if you're using degrees as the angle, make sure your calculator is in Degree mode first, thus tan(39) will mean "tangent of 39 degrees".
[tex]\bf 8\cdot tan(39~rad) \approx 28.9~\hspace{10em} \cfrac{8\cdot sin(39~rad)}{sin(51~rad)}\approx 11.5[/tex]
Vinyl wallpaper is needed to cover 4 walls of a room each wall measures 12 feet By 8 feet and each bolt of wallpaper covers 72 square feet deduct 52 square feet for windows and the door if the wallpaper costs $13.90 per bolts how much will the paper cost
Answer:
$69.50
Step-by-step explanation:
First you need to know how much wall you're going to cover.
Each wall us 12 ft by 8ft
The area of a rectangle can be computed with the formula:
A = L x W
Using the given:
A = 12ft x 8 ft
= 96 ft²
This is the area of each wall. Since all 4 walls will be covered, you multiply the area of 1 wall by 4.
96 ft² x 4 = 384 ft²
Next we subtract the area of the windows and the door because we won't be covering that.
384 ft² - 52 ft² = 332 ft²
So the total area we are covering with wall paper is 332 ft².
To get the cost of the wallpaper needed, we just need to compute first how many bolt we will need. Divide the total area to be covered by the area of one bolt of wall paper.
332 ft² ÷ 72 ft²/bolt = 4.61 bolts ≅ 5 bolts
Then we multiply it by the price per bolt:
5 bolts x $13.90/bolt = $69.50
13x + 3y = 15 and y = 5 - 4x.
A. x = 0, y = 5
B. x = 5, y = 0
C. x = 9, y = -31
Pleaseee explain with words and number pleasee thank you so much
A. X=0 Y=5
Those 2 equations are a system. You answer is the value of x and y.
13x+3y=15
y=5-4x
First, lets make each equation fit into y=mx+b
13x +3y=15 y=5-4x
-13x -13x y=-4x+5
3y= -13x +15
Let's use the elimination method to solve this.
y= -4x+ 5 multiply top by 3
3y=-13x+15
3y=-12x+15
3y=-13x+15 subtract the equations
0=x
Lets use the x we just found to solve for y.
y=4x+5
y=4(0)+5
y=5
What are the solutions of the following system
Answer:
(-6, 312), (6, 312)Step-by-step explanation:
[tex]\left\{\begin{array}{ccc}10x^2-y=48\\2y=16x^2+48&\text{subtracy}\ 16x^2\ \text{from both sides}\end{array}\right\\\\\left\{\begin{array}{ccc}10x^2-y=48\\-16x^2+2y=48&\text{divide both sides by 2}\end{array}\right\\\underline{+\left\{\begin{array}{ccc}10x^2-y=48\\-8x^2+y=24\end{array}\right}\qquad\text{add both sides of the equations}\\.\qquad2x^2=72\qquad\text{divide both sides by 2}\\.\qquad x^2=36\to x=\pm\sqrt{36}\\.\qquad x=\pm6\\\\\text{Put the values of}\ x\ \text{to the second equation}[/tex]
[tex]2y=16(\pm6)^2+48\\\\2y=16(36)+48\\2y=576+48\\2y=624\qquad\text{divide both sides by 2}\\y=312[/tex]
Need Help Answer Please!!
Answer:
The correct option is B
Step-by-step explanation:
The equation of a line in point-slope form is:
y-y1 = m(x-x1)
where m is the slope and (x1,y1) a point on the line
here m=2 and (x1,y1)=(2,3)
substitute these values into the equation.
y-3 =2(x-2)
Thus the correct opttion is B....
Find the missing angle measure in each triangle. Show your work.
Answer:
see explanation
Step-by-step explanation:
The sum of the 3 angles in a triangle = 180°
Subtract the sum of the 2 given angles from 180 for third angle
∠C = 180° - (50 + 75)° = 180° - 125° = 55°
∠B = 180° - (60 + 30)° = 180° - 90° = 90°
∠A = 180° - (45 + 30)° = 180° - 75° = 105°
The required measure of the angle for the given triangles is given as ∠C = 55°, ∠B = 90° and ∠A = 105°
What is the triangle?The triangle is a geometric shape that includes 3 sides and the sum of the interior angle should not be greater than 180°
Here,
The sum of the 3 angles in a triangle = 180°
Subtract the sum of the 2 given angles from 180 for the third angle
∠C = 180° - (50 + 75)°
= 180° - 125°
= 55°
Similarly,
∠B = 90°
∠A = 105°
Thus, the required measure of the angle for the given triangles is given as ∠C = 55°, ∠B = 90° and ∠A = 105°
Learn more about triangles here:
https://brainly.com/question/2773823
#SPJ5
What is the distance between the points (-4, -12) and (-4, 22) in the coordinate plane?
Answer:
34
Step-by-step explanation:
You can use the distance formula to find the distance between any two points in the coordinate plane.
For this problem, you can use a simpler method since both points have the same x-coordinate. Two points than have the same x-coordinate are on the same vertical line. The distance between them is the absolute value of the difference between the y-coordinates.
distance = |-12 - 22| = |-34| = 34
Answer:
34
Step-by-step explanation:
By the distance formula:
[tex]D = \sqrt{[-4-(-4)]^2 + (22-(-12))^2} = \sqrt{34^2} = |34| = 34[/tex]
Write a function rule for the table.
x ƒ(x)
3 –1
4 0
5 1
6 2
Answer:
Step-by-step explanation:
When one variable depends on another variable according to a rule it is known as function:
For example if you want an output of 2 and the input value is 4. Then you will subtract 4 from x
We have to find x f(x).
x f(x) =?
f(x) = x-4
Now input value is: x= 3
x f(x)
3 (x-4)
3 (3-4)
3 -1
Now x= 4
x f(x)
4 (x-4)
4 (4-4)
4 0
Now x=5
x f(x)
5 (x-4)
5 (5-4)
5 1
Now x=6
x f(x)
6 (x-4)
6 (6-4)
6 2 ....